A case study: Concurrent palliative care based on SENS‐structure for patients with advanced prostate cancer. Issue 2 (6th April 2020) - Fliedner, Monica; Willener, Rita
Abstract: On an acute urological ward, it is challenging to meet all needs of patients with life‐limiting progressive cancer disease in complex situations. The focus shifts from curation to the holistic palliative approach aiming at patients' and their families' needs and planning care in advance with an interprofessional attitude. Based on a patient with castration refractory prostate carcinoma with multiple metastasis, the aim of this case study is to describe the palliative care approach, using the established so‐called SENS‐structure (Symptoms, End‐of‐life decisions, Network and Support of the carer) in which the bio‐, psycho‐, social and spiritual needs are addressed. We report on our practice experience using the SENS‐structure, in which the team discusses palliative care interventions with patients and their family: management of (potential) symptoms and self‐supporting strategies, expectations and end‐of‐life decisions including advance care planning, evaluation of patients' social and professional network and setting up additional support. The palliative care team provides advice to the treating team on future treatment strategies and care activities. The complex situation of a patient with metastatic prostate cancer and his personal sufferings illustrate the interprofessional use and person‐centred focus of the SENS‐structure. Important in this phase is—next to the family carers—the involvement of all professions and disciplines to break down the complexity of the situation into manageable proportions. Early involvement of palliative care for patients with advanced cancer is highly recommended. The SENS‐structure helps to prioritize and include the personalized approach which is strongly supported by nurses.